ВЛИЯНИЕ АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИ НА КАЧЕСТВ О ЖИЗНИ БОЛЬНЫХ БРОНХИАЛЬНОЙ АСТМОЙ - Л. В. Бердникова; И. С. Добротина; Н. Н. Боровков (SINAPS LLC, 2016)
The factors supposed to influence on the quality of life in patients with bronchial asthma and arterial hypertension had been examined. MOS SF-36 v2 questionnaire was used. Age, sex, country life, association of the professional occupation with stress had been contributed to decrease in quality of life. Bronchial obstruction and long asthma history correlated with worse parameters of SF-36 v2. Arterial hypotension lower than 120 mm Hg against the background of antihypertensive therapy correlated with decrease in quality of life.